STEAM education for preschool students: Patterns, activity designs and effects - Suthasini BUREEKHAMPUN; Torfhun MUNGMEE (My University, 2020)
Organizing STEAM educational activities which integrate different knowledge areas in order to create an innovation for primary school students that uses many skills is difficult. This is because children aged 6 are different in terms of intelligence, skills and mood. There is a lack of a set of activities that make students happily learn together by playing and get involved with creative and innovative thinking, practice planning and decision skills, and work together as a team. Therefore, encouragement is needed to create a set of learning activities by applying the STEAM educational concept and to evaluate their learning success also using the STEAM educational concept. The result of this set of activities was the design of three different moveable robot inspired by a breed of dog called Beagle. The Beagle set of activities were then evaluated by three experts in the area. The outcome was that the first design had the highest mean (X ̅= 4.88, S.D. = 0.17). The mean from the structure & control system evaluation of this set of activities was at a very good level (X ̅=4.83, S.D.= 0.39). Finally, the learning achievement from using this set of STEAM educational activities with the sample had a mean of 16.07, which is 80.33 %. This means that the proposed set of activities is able to help students to improve the process of their thought. However, the outcome is based on the nature, experience and learning method of each student.
Keywords: Technician; Educational Methods and Outcomes